Sebaceous Lymphadenoma of Parotid: Imaging, Cytological, and Histological Findings in Detail - Golsa Shekarkhar; Hossein Soleimanpour; Seyed Hamed Jafari; Fatemeh Zamani (Hindawi Limited, 2018)
Sebaceous lymphadenomas are rare and account for less than 1% of primary salivary gland tumors. These rare tumors are mostly found in men older than 50 years. The clinicopathological features of these tumors are poorly understood and no definite causative factor has been reported for them till now. They are not often diagnosed prior to surgery, which could be due to their rarity and lack of enough preop radiological and cytological findings. Few case reports have been published in literature about their pathogenesis and accompanying malignant lesions. The cytological and imaging findings have been dealt with in some articles. Here we describe the histologic, cytologic, and radiologic findings of sebaceous lymphadenomas of parotid gland, all together, and discuss their differential diagnoses in various diagnostic methods.